Serials Spoken Here. Issue 1 (3rd April 2022) - Dawson, Jill; Dennis, Sarah; Colquitt, Michelle; Corrigan, Brian; Shank, Jonathan; Thornton, Bonnie
Abstract: This column reports on sessions from the Charleston Conference 2021. Topics covered include handling compliance and tracking publishing activities for open research, perspectives from the NISO working group on proposed journal package identifiers, and improvements made by librarians and publishers to ebooks for print disabled user access. Trends in troubleshooting e-resources issues such as proactive link checking, an assessment of e-resources user errors and their corresponding themes, and libraries implementing Open Athens and Seamless Access are also shared.